CIVIL SOCIETY PARTICIPATION IN THE MBOMBELA LOCAL MUNICIPALITY - NKWINIKA, THEMBA (My University, 2011)
Public participation and the free existence of civil society organisations capable of interfacing with governance practices are accepted as some of the essential elements of a democratic system of governance. Thus, democratic states should have systems of governance that entrench mechanisms for public and civil society participation in the legislative processes at all spheres or levels of government. The epoch making 1994 general elections and the adoption of the new Constitution in 1996 turned South Africa into a democratic republic. The Constitution marked a significant shift from an authoritarian apartheid state to a democratic one where civil liberties are assured. The 1996 Constitution introduced many changes on governance in South Africa two which are worth mentioning in this study. Firstly, local government is considered as a sphere of government as opposed to a tier of government. Secondly, public and civil society participation is provided for in the three spheres of government. The constitution expresses this more clearly for the local government sphere by defining public and civil society participation as one of the objects. Consistent with this, municipalities are expected to develop a governance culture that promotes the involvement of individuals and organised groups in their decision making. To this end, structures such as ward committees and other issue specific representative forums have been put in place to promote public participation in municipal processes. However, the participation of civil society organisations in municipal processes remains blurred. This study investigates the current levels of civil society engagement in local governance by looking at the involvement of Non-Governmental Organisations (NGOs) and Community-Based-Organisations (CBOs) in the Mbombela municipality in the Mpumalanga Province. To achieve this, the study investigates the participation of civil society organisations in the following municipal processes: local economic development planning (LED), integrated development planning (IDP), municipal budgeting, and service delivery in Mbombela municipality. Qualitative research methodology was used in conducting the study. The study employed a combination of interviews and documental review to solicit data on civil society participation the Mbombela municipality. VI The study observed that there were low levels of civil society participation in municipal processes in the Mbombela municipality. During the study, it was discovered that it was in the only in the Local AIDS Council that civil society organisations in Mbombela had a representation. The other participatory forums such and the IDP representative forums had no civil society representation. The study further observed that the Mbombela municipality did not have a tailor-made process that would facilitate the involvement of civil society in its governance processes. Civil society organisations in Mbombela on the other hand appear not to be making efforts to participate in municipal decision making processes. Based on the findings the study makes recommendations to the civil society, local, provincial, and national governments as well as the research community on how each stakeholder can contribute towards the enhancement of civil society organisations. For the three spheres of government, recommendations are made on each sphere‟s contribution towards the development of mechanisms and systems that need to be in place to promote civil society participation in local government. For civil society, recommendations are made on the need for civil society to claim its stake on municipal governance. For the research community, areas for research as a way to contribute on the ongoing scholarly discourse on civil society participation in local government are recommended.
MM thesis - P&DM
Keywords: Civil society; Local authorities; Local government; Municipalities